2017
DOI: 10.1177/1524839917741485
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Tobacco Control Media Campaigns Among Smokers With Lower Socioeconomic Status

Abstract: People with low socioeconomic status (SES) in the United States have disparately high rates of smoking and experience disproportionately high burdens of smoking-related disease. Tobacco control media campaigns are a critical strategy for reducing tobacco use prevalence, but evidence is mixed about the optimal use of mass media to reach and promote tobacco use cessation among people with low SES. Improved understanding of the factors influencing how low-SES tobacco users evaluate tobacco control media campaigns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…A qualitative study on anti-smoking messages found culturally-targeted messages were more appealing to lower income smokers than other messages 67 . However, these low-SES smokers also reported scepticism about cessation messages and barriers to quitting related to stress, social contexts, and addiction 83 . Among blue collar construction workers, smoking cessation ads that emphasized family and work and presented smoking harms in the context of work hazards were more appealing than other messages 84 .…”
Section: Resultsmentioning
confidence: 98%
“…A qualitative study on anti-smoking messages found culturally-targeted messages were more appealing to lower income smokers than other messages 67 . However, these low-SES smokers also reported scepticism about cessation messages and barriers to quitting related to stress, social contexts, and addiction 83 . Among blue collar construction workers, smoking cessation ads that emphasized family and work and presented smoking harms in the context of work hazards were more appealing than other messages 84 .…”
Section: Resultsmentioning
confidence: 98%
“…Message engagement. The most occurring theme concerned message engagement, with a focus on how relatable a HII message is to its targeted population [18,26,30,34,37,38,51]. McCullough et al [37] and Veldheer [18] suggested that their participants' distrust of the HII source and preference for lay over expert knowledge may have reduced the intervention's effectiveness.…”
Section: Thematic Analysismentioning
confidence: 99%
“…These themes are consistent within the broader literature on the factors important for establishing institutional trust [ 24 , 37 ]. In a formative qualitative study designed to inform program planning for the Connecticut Tobacco Control Program, McCullough and colleagues [ 38 ] conducted focus groups with primarily low SES adults who reported currently smoking. Though not explicitly focused on trust in tobacco control itself, their analysis suggested that participants distrusted tobacco control and held “negative attitudes about the tobacco industry’s and government entities’ perceived roles in sponsoring tobacco control campaigns” collaboratively, rendering ads untrustworthy and calling into question the motivations of tobacco control ([ 38 ] p. 553).…”
mentioning
confidence: 99%
“…In a formative qualitative study designed to inform program planning for the Connecticut Tobacco Control Program, McCullough and colleagues [ 38 ] conducted focus groups with primarily low SES adults who reported currently smoking. Though not explicitly focused on trust in tobacco control itself, their analysis suggested that participants distrusted tobacco control and held “negative attitudes about the tobacco industry’s and government entities’ perceived roles in sponsoring tobacco control campaigns” collaboratively, rendering ads untrustworthy and calling into question the motivations of tobacco control ([ 38 ] p. 553). As trust in tobacco control is dependent in part upon perceptions of benevolence—the notion that the government is acting in the best interest of the public ([ 24 ], p. 625)—these preliminary findings, if widespread, have serious implications for the effectiveness of tobacco control efforts.…”
mentioning
confidence: 99%